Dinamika Pengelolaan Zakat Berbasis Organisasi Masyarakat dalam Pemberdayaan Masyarakat - Fathaniyah, Lidia; Makhrus, M (Alhamra Jurnal Studi Islam, 2023)
Indonesia is one of the countries with growing management of zakat. Based on Law No. 23 of 2011 concerning zakat management, there are two types of zakat management organizations in Indonesia: BAZNAS and LAZ. This study aims to identify community organization-based zakat management in community empowerment in Banyumas Regency. This research used a type of field research with a descriptive qualitative approach and was conducted at LAZISMU and LAZISNU in Banyumas Regency, while data was obtained through interviews, observation, and documentation. While the data analysis was carried out deductively to obtain natural events in the field which then obtained a conclusion and presented in a descriptive form. The results of this study reveal that the management of zakat in community empowerment has developed dynamically over a long period Community organization-based zakat management in the form of community empowerment has a supporting factor in the form of high community enthusiasm and an inhibiting factor in the form of a lack of human resources who can manage zakat for community empowerment.